Drone-Based Hyperspectral and Thermal Imagery for Quantifying Upland Rice Productivity and Water Use Efficiency after Biochar Application - Jin, Hongxiao (2021)
Se seleccionó la licencia Creative Commons para este envío. El documento trae lo siguiente: © 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access articledistributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/). (En caso de duda consultar a Meilyn Garro).